Simplification of ensemble averaged two-phase flow with heat and mass transfer equations for boiling in a channel - Aybar, Hikmet S.; Sharifpur, Mohsen (Trans Tech Publications Ltd, 2008)
Generation of vapor and predication of its behavior is an important problem in many industries. In this study, the three dimensional governing equations for turbulence two-phase flow are derived using ensemble averaging two fluid model. The governing equations are simplified by a heuristic approach based on boiling data, and the equations are used to obtain the parameters for each phase along the channel. A computer program is written for the simplified one-dimensional equations, and the results are compared with experimental data.
3rd International Conference on Diffusion in Solids and Liquids -- JUL 04-06, 2007 -- Algarve, PORTUGAL
Keywords: two-phase flow; heat and mass transfer; boiling; two-fluid model